The Study of Trends and Out Come of Acute Poisoning in a Tertiary Care Hospital Khammam, Telangana; India (Medico Legal Update, 2020)
Background and Objective: It is important to know the trends, nature, sevesrity and outcome of acutepoisoning cases in order to take up appropriate planning, time lapse, first aid and recovery. This study is toassess the trends and outcome of acute poisoning cases in a tertiary care hospital in Khammam.Materials and Methods: This is a retrospective study conducted in a tertiary care hospital attached to amedical institution in Khammam. The study includes 126 cases and data regarding age, sex, time elapsedafter intake, circumstances of poisoning, name of the poisonous substance, chemical type, duration ofhospitalization, severity and outcome collected in the Proforma.Results: Incidence was common among 21-30 yr. old married Hindu male laborers from rural backgroundbelonging low socioeconomic classes with only primary education. Majority of the incidents occurred inthe victim’s home during the day time. Maximum number of cases were encountered during the Rainyseason and in the month of November. Organophosphorus insecticides and poisoning by snake bite werethe commonest types of poisoning. Majority of the acute poisoning cases were hospitalized within one hourof toxic exposure. Maximum number of patients stayed in hospital for up to 7 days and recovered. Familyproblems and financial problems were the most common reasons behind poisoning. Overall mortality wasfound to be 3.05% and 38 cases succumbed to the poisoning.Conclusion: Poisoning was common in young males. Maximum number of cases encountered in Rainyseason. Organophosphorus insecticides and poisoning by snake bite were the commonest types of poisoning.Majority of the acute poisoning cases were hospitalized within one hour of toxic exposure. The overallmortality was substantially high, mainly contributed by self-poisoning with insecticides. Early care in atertiary care center may help to reduce mortality in India.